Journaling: A Cross-cultural Approach to Transcend Individual Limitations Among Learners - Pandey, Kashi Raj (Journal of Education and Research, 2013)
While writing and reading have certain specific uses in the broader aspect of life and cultural practices, this paper focuses on improving a researcher’s practice as a teacher and learner in inclusiveness, multiplicity, multiculturalism, and possibility of various perspectives in any given contexts. Taking auto-ethnography as a methodological referent in writing narratives, that deals with my own and students’ lived experiences about journaling and its impact on transformation, this research looks into the dialectical nature of knowing through reflection about self practices whilst taking the cultural context of teaching in multiple perspectives. Responding to a number of questions including how a habit of maintaining journal helps the practitioner in cherishing multicultural thoughts, this work is equally a room that tries to find answers to the research question-- When and how do the learners realize a need for cross-cultural understanding? Along with participants’ narratives and other related theories this paper also covers the researcher’s encounter with Dr. Inspection, and a letter to the Subject Committee. In addition, an acrostic poem and a Haiku also give the picturesque of the ongoing discourse among teachers and students, teachers and management and management and students in any educational institutions being Mount Kailash University (MKU)1, a prototype. DOI: http://dx.doi.org/10.3126/jer.v3i0.7854 Journal of Education and Research March 2013, Vol. 3, No. 1, pp. 75-91